Inefisiensi Relaas Panggilan Surat Tercatat pada Pengadilan Negeri Kasongan (International Forum of Researchers and Lecturers, 2025)
Registered letter summons plays an important role in the judicial system as a form of official notification to the parties involved in a case. However, at the Kasongan District Court, the process of sending summons releases still faces various obstacles that cause inefficiency, especially related to geographical factors, inaccuracy of destination addresses, and delays in delivery services. This study aims to analyze the factors that cause inefficiency in the delivery of registered letters and explore solutions that can improve the effectiveness of the summons system. The research method used is a normative sociological approach, which examines related regulations and the social impact of the ineffectiveness of the summons system. The results of the study indicate that geographical obstacles, imperfect address recording systems, and limited coordination between the court and delivery service providers are the main factors in summons inefficiency. To overcome these obstacles, it is necessary to implement technology optimization through an electronic summons system (e-Summon) and improve coordination with delivery service providers to ensure more accurate and efficient delivery of summons releases. With the reform of the summons system, it is hoped that the effectiveness of the trial can be increased and the principle of a simple, fast, and low-cost trial can be realized.